2008
DOI: 10.2527/jas.2007-0371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary arginine supplementation during gestation and lactation on the performance of lactating primiparous sows and nursing piglets1

Abstract: A 2 x 2 factorial arrangement of treatments in a randomized block design was used to determine the effects of dietary Arg supplementation during gestation and lactation on the lactation performance of 38 first-parity sows. At 30 d of gestation, pregnant gilts were allotted based on BW to 1 of 2 diets supplemented with 1% L-Arg.HCl or 1.7% L-Ala (isonitrogenous control). After farrowing, sows were further allotted based on BW within previous gestation treatment groups to 1 of 2 lactation diets supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
100
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 47 publications
16
100
2
1
Order By: Relevance
“…This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction. The performance of all sows in this study was normal, which is similar to our previous publications, with regard to BW gain during gestation, BW changes during lactation, feed intake during gestation and lactation, litter size, litter birth weight and litter weight gain (Mateo et al, 2007(Mateo et al, , 2008(Mateo et al, and 2009Kim et al, 2009). In this study, there was no truly non-pregnant sow to compare the oxidative damage with pregnant sow because of practical difficulty in obtaining non-pregnant sows with similar age, parity and BW to those used in this study.…”
Section: Discussionsupporting
confidence: 89%
“…This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction. The performance of all sows in this study was normal, which is similar to our previous publications, with regard to BW gain during gestation, BW changes during lactation, feed intake during gestation and lactation, litter size, litter birth weight and litter weight gain (Mateo et al, 2007(Mateo et al, , 2008(Mateo et al, and 2009Kim et al, 2009). In this study, there was no truly non-pregnant sow to compare the oxidative damage with pregnant sow because of practical difficulty in obtaining non-pregnant sows with similar age, parity and BW to those used in this study.…”
Section: Discussionsupporting
confidence: 89%
“…L-Arginine is an important substrate for NO, and increasing the supply of Arg to the mammary gland could have a positive effect on total AA supply. Indeed, Mateo et al (2008) observed a higher total protein concentration in milk of lactating sows supplied with extra Arg compared to sows on a control diet. However, this effect was only apparent in the first week of lactation.…”
Section: Factors Affecting the Efficiency Of N Utilization In The Mammentioning
confidence: 94%
“…Arginine stimulates the secretion of prolactin and growth hormone (ReYeS et al, 1994) and participates in angiogenesis in mammary tissue (MATeO et al, 2008). Due to the effects of arginine on nitric oxide production and vasodilation, this amino acid causes an increase in local blood flow, resulting in higher nutrient supply which could increase milk production (TROTTIeR et al, 1997;WU & MeININGeR, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, research efforts have been directed toward reviewing the nutritional requirements of sows from modern genetic lines at various levels: in the energy and amino acid content of diets, ratios of other amino acids to lysine according to the stage of production, as well as the individual supplementation of some amino acids via top-dressing (KIM et al, 2004;MATeO et al, 2008;YANG et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation